2019
DOI: 10.1080/13683500.2019.1657811
|View full text |Cite
|
Sign up to set email alerts
|

The ‘volunteer tourist gaze’: commercial volunteer tourists’ interactions with, and perceptions of, the host community in Cusco, Peru

Abstract: This paper presents the commodified volunteer tourist gaze through the use of a case study which contextualises commercial volunteer tourism. Interviews undertaken with volunteer tourists in Cusco, Peru, and on-the-ground participant observation, provide insights into what we term a 'volunteer tourist gaze' underpinned by neo-colonial tendencies. The findings demonstrate that volunteer tourists are not passive consumers of a destination, but actively engaged in a multi-sensory, embodied experience. This is evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Yet there are many criticisms of volunteer tourism's role in development, particularly in the Global South. Godfrey, Wearing, and Schulenkorf (2015) argue that volunteer tourism has been packaged by an industry for the neo-liberal consumption by white, well-educated, young people. In this vein volunteer tourism is viewed as postcolonial Western domination in development processes (Devereux, 2008;Eddins, 2013;Palacios, 2010;Vrasti, 2013).…”
Section: Volunteer Tourismmentioning
confidence: 99%
“…Yet there are many criticisms of volunteer tourism's role in development, particularly in the Global South. Godfrey, Wearing, and Schulenkorf (2015) argue that volunteer tourism has been packaged by an industry for the neo-liberal consumption by white, well-educated, young people. In this vein volunteer tourism is viewed as postcolonial Western domination in development processes (Devereux, 2008;Eddins, 2013;Palacios, 2010;Vrasti, 2013).…”
Section: Volunteer Tourismmentioning
confidence: 99%
“…Through this research, I hoped to carve a path for investigation into international volunteers’ picturing and posting practices, a topic which is increasingly salient for visual and non-visual scholars alike. For example, while Godfrey et al (2020) centered their analysis around the commercial dimensions of volunteer tourism in Peru, the lead author observed that some volunteers were keen to photograph local children and that other volunteers judged them negatively for such conduct, with one participant remarking: “it makes me kind of ‘eargh’, it’s almost kind of poverty tourism. .…”
Section: Discussionmentioning
confidence: 99%
“…Considered initially as a niche type of tourism (Stainton, 2016), its popularity has since grown (Kainthola et al, 2021), and it is now classified as a phenomenon under "mass niche" (Thompson & Taheri, 2020). For example, volunteer tourism is considered one of the main subtypes of "research related tourism" (Shah et al, 2022) or scientific tourism (Godfrey et al, 2015) whenever it "involves elements of research" or "knowledge acquisition through learning and practicing new tasks". It means that scientists may engage in a volunteer organisation's project as its leaders (Shah et al 2022).…”
Section: Volunteer Tourism Defining Processmentioning
confidence: 99%